2020
DOI: 10.1177/0093854820908628
|View full text |Cite
|
Sign up to set email alerts
|

Do Judicial Instructions Aid in Distinguishing Between Reliable and Unreliable Jailhouse Informants?

Abstract: Jailhouse informants are a leading cause of wrongful convictions. In an attempt to preempt such miscarriages of justice, several states (e.g., Connecticut and California) have mandated that judicial instructions be provided to act as a safeguard against false testimony. This study evaluated the effectiveness of these instructions in helping jurors distinguish between reliable and unreliable jailhouse informants. Participants read a trial transcript that varied instructions (Standard, Connecticut, Enhanced) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In the present study, we constructed four cognitive networks to represent the deliberations of each type of trial that involved a jailhouse informant (that is, incentive, no incentive) for both a guilty verdict and a not-guilty verdict. Consistent with data from mock juror research (for example, Wetmore et al, 2020) asking why participants rendered a guilty verdict, the deliberation networks from jailhouse informant mock juries (both incentive and no incentive) that rendered guilty verdicts focused on the reliability of the jailhouse informant. These networks also showed how other comments about the jailhouse informant and the defendant's guilt were connected.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In the present study, we constructed four cognitive networks to represent the deliberations of each type of trial that involved a jailhouse informant (that is, incentive, no incentive) for both a guilty verdict and a not-guilty verdict. Consistent with data from mock juror research (for example, Wetmore et al, 2020) asking why participants rendered a guilty verdict, the deliberation networks from jailhouse informant mock juries (both incentive and no incentive) that rendered guilty verdicts focused on the reliability of the jailhouse informant. These networks also showed how other comments about the jailhouse informant and the defendant's guilt were connected.…”
Section: Discussionmentioning
confidence: 82%
“…Research on jailhouse informants, like other system variable research, is therefore “likely to produce findings that improve the quality of the decisions that jurors render, influence policy, and increase the justice that defendants and victims receive” (Kovera, 2017, p. 290; see also Steblay, 2019). This research should expand on the limited number of investigations that have examined the impact of special jury instructions regarding jailhouse informant testimony (but see Wetmore et al, 2020), and whether jurors are affected by expert testimony on jailhouse informants (but see Maeder & Pica, 2014; Neuschatz et al, 2012), as well as investigating the motivations of prosecutors who employ jailhouse informants (see Joy, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closely related to the persuasiveness of prison informant testimony, empirical evidence suggests that judicial directions do not provide protection against reliability concerns. For example, Wetmore et al (2020) found that even ‘enhanced’ jury instructions ‘had no effect on verdict decisions when a jailhouse informant testified’ (at 597; see, further, DeLoach et al, 2020). The other main feature of trial with the potential to inform jury assessment of reliability is cross-examination of the informant.…”
Section: Prison Informant Reliability Concerns: a Primermentioning
confidence: 99%
“… 33. W v R , above n. 3 at [84]–[85] ( per majority); [246] ( per minority). Much of this research is recent, post-dating the NZ Evidence Act—notably, the studies by Wetmore et al (2020) and DeLoach et al (2020) discussed above. It is also the case that much more research on this point is needed; as the minority noted, the research currently does not make the case for jettisoning reliance on judicial directions altogether (at [246]). …”
mentioning
confidence: 99%